Предмет: Алгебра,
автор: maxcv
Найдите F(1), если F(x) - первообразная для f (x), f (x) = 2x+3 и F(3)=12
Ответы
Автор ответа:
0
F(x) = ∫ f(x) = ∫ (2x + 3)dx = x^2 + 3x + C
F(3) = 9 + 3*6 + C = 18 + C = 12
C = 12 - 18 = - 6
F(x) = x^2 + 3x - 6
F(1) = 1^2 + 3 - 6 = - 2
F(3) = 9 + 3*6 + C = 18 + C = 12
C = 12 - 18 = - 6
F(x) = x^2 + 3x - 6
F(1) = 1^2 + 3 - 6 = - 2
Похожие вопросы
Предмет: Русский язык,
автор: edgarnasakin
Предмет: Математика,
автор: Sftfcgrdzbgg
Предмет: Математика,
автор: Аноним
Предмет: Геометрия,
автор: Аноним
Предмет: Математика,
автор: enot991